PELAKSANAAN PROGRAM KAMPUNG KELUARGA BERENCANA MERANTI MANDIRI KELURAHAN MERANTI PANDAK KECAMATAN RUMBAI PESISIR KOTA PEKANBARU TAHUN 2019 - Dian Eka Pertiwi; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The high rate of population growth in Indonesia makes the government need to strengthen the Population, Family Planning, and Family Development (KKBPK) program. Kampung Keluarga Berencana is present in the realm of national development and is one of the government's flagship programs. Kampung Keluarga Berencana is a regional unit that has certain criteria, where there is an integration of population programs, family planning, family development, and related sector development that is carried out systematically. Kampung Keluarga Berencana is one of the models chosen by the President to be a role model for hamlets, villages to realize the norms of quality, happy, and prosperous small families. The purpose of this research is to describe the implementation of the Kampung Keluarga Berencana Meranti Mandiri program in Meranti Pandak Village in 2019 and analyze the factors that influence the implementation of the Meranti Mandiri Family Planning Program, namely program elements, implementing organization elements, and target group elements. This research is descriptive research with a qualitative approach. The location of this research was conducted in Kampung Keluarga Berencana Meranti Mandiri Village Meranti Pandak District Rumbai Pesisir, Pekanbaru City. Data collection techniques are carried out through interviews and documentation. Data analysis techniques used are data collection, data reduction, data presentation, and conclusion. The results of this study concluded that the implementation of theKampungKeluargaBerencanaMeranti Mandiri program in Meranti Pandak Village in 2019was seen through program elements, and the implementing elements of the program were not yet fully optimal. This is because the implementation of Kampung KB Meranti Mandiri does not meet all the characteristics that affect the successful implementation of the program such as not all activity groups and working groups that are realized, the unavailable business units of community empowerment, and insufficient budget availability. Keywords: Kampung Keluarga Berencana, Program, Implementing Organization, Target Group